Vaccine Effectiveness Estimates, 2004–2005 Mumps Outbreak, England - Cohen, Cheryl (Centers for Disease Control and Prevention, 2007)
The United Kingdom and United States have recently experienced large outbreaks of mumps, which raises concerns about vaccine effectiveness. The effectiveness of the mumps component of the measles, mumps, rubella (MMR) vaccine was estimated using the screening method. In England from January 2004 through March 2005, 312 cases of mumps were reported in children eligible to have received 2 doses of MMR vaccine. Of these children, 52 (16.7%) had received 1 dose of MMR vaccine, and 97 (31.1%) had received 2 doses. Vaccine effectiveness was 88% (95% confidence interval [CI] 83%–91%) for 1 dose and 95% (95% CI 93%–96%) for 2 doses. The effectiveness of 1 dose declined from 96% (95% CI 81%–99%) in 2-year-olds to 66% (95% CI 30%–83%) in 11- to 12-year-olds, and the effectiveness of 2 doses declined from 99% (95% CI 97%–99.5%) in 5- to 6-year-olds to 86% (95% CI 74%–93%) in 11- to 12-year-olds (p<0.001 for 1 or 2 doses). Waning immunity may contribute to mumps outbreaks in older vaccinated populations.